229k views
0 votes
the equation a=1/2(b1+b2)h can be used to determine the area, a, of a trapezoid with height, h, and base lengths, b1 and b2. which are equivalent equations? check all that apply.

the equation a=1/2(b1+b2)h can be used to determine the area, a, of a trapezoid with-example-1
User Sbywater
by
5.8k points

2 Answers

6 votes

Answer:

b₁ = (2a – b₂h)/h; b₁ = (2a)/h – b₂; h = (2a)/(b₁ + b₂)

Explanation:

A. Solve for b₁

a = ½(b₁ + b₂)h Multiply each side by 2

2a = (b₁ + b₂)h Remove parentheses

2a = b₁h + b₂h Subtract b₂h from each side

2a - b₂h = b₁h Divide each side by h

b₁ = (2a – b₂h)/h Remove parentheses

b₁ = (2a)/h – b₂

B. Solve for h

2a = (b₁ + b₂)h Divide each side by (b₁ + b₂)

h = (2a)/(b₁ + b₂)

User Inaps
by
5.5k points
3 votes

Answer:

(A) and (D)

Explanation:

It is given that the given expression
a=(1)/(2)(b_(1)+b_(2))hcan be used to determine the area, a, of a trapezoid with height, h, and base lengths
b_(1) and
b_(1).

Thus, solving the given equation and finding the value of
b_(1), we get


a=(1)/(2)(b_(1)+b_(2))h


(2a)/(h)-b_(2)=b_(1)

And the expression for height is:


2a=(b_(1)+b_(2))h


h=(2a)/((b_(1)+b_(2)))

(A) The given expression is:


(2a)/(h)-b_(2)=b_(1)

which is equivalent to the given expression, therefore this option is correct.

(B) The given expression is:


(a)/(2h)-b_(2)=b_(1)

which is not equivalent to the given expression, therefore this option is not correct.

(C) The given expression is:


(2a-b_(2))/(h)=b_(1)

which is not equivalent to the given expression, therefore this option is not correct.

(D) The given expression is:


(2a)/(b_(1)+b_(2))=h

which is equivalent to the given expression, therefore this option is correct.

(E) The given expression is:


(a)/(2(b_(1)+b_(2)))=h

which is not equivalent to the given expression, therefore this option is not correct.